Adaptive Lipid Immiscibility and Membrane Remodeling Are Active Functional Determinants of Primary Ciliogenesis. Issue 2 (16th December 2020) - Bernabé‐Rubio, Miguel; Bosch‐Fortea, Minerva; García, Esther; Bernardino de la Serna, Jorge; Alonso, Miguel A.
Abstract: Lipid liquid–liquid immiscibility and its consequent lateral heterogeneity have been observed under thermodynamic equilibrium in model and native membranes. However, cholesterol‐rich membrane domains, sometimes referred to as lipid rafts, are difficult to observe spatiotemporally in live cells. Despite their importance in many biological processes, robust evidence for their existence remains elusive. This is mainly due to the difficulty in simultaneously determining their chemical composition and physicochemical nature, whilst spatiotemporally resolving their nanodomain lifetime and molecular dynamics. In this study, a bespoke method based on super‐resolution stimulated emission depletion (STED) microscopy and raster imaging correlation spectroscopy (RICS) is used to overcome this issue. This methodology, laser interleaved confocal RICS and STED‐RICS (LICSR), enables simultaneous tracking of lipid lateral packing and dynamics at the nanoscale. Previous work indicated that, in polarized epithelial cells, the midbody remnant licenses primary cilium formation through an unidentified mechanism. LICSR shows that lipid immiscibility and its adaptive collective nanoscale self‐assembly are crucial for the midbody remnant to supply condensed membranes to the centrosome for the biogenesis of the ciliary membrane. Hence, this work poses a breakthrough in the field of lipid biology by providing compelling evidence of a functional role for liquid ordered‐like membranes in primary ciliogenesis. Abstract : A method developed to track space‐time lipid self‐assembly in live cells by simultaneously determining lateral lipid packing and micro‐ and nanoscale dynamics reveals that the condensed nano‐ and micro‐domains associated with the midbody remnant are remodeled and they actively self‐assemble to provide lipids to the centrosome for ciliary membrane assembly, a fundamental as yet unsolved biological process.